PENGARUH FREKUENSI MAKAN TERHADAP JAM KERJA PENEBANG JATI DI KPH JOMBANG - Maman Mansyur Idris; Sona Suhartana (Jurnal Penelitian Hasil Hutan, 1987)
One of heavy work in the forestry activity in Indonesia  is manual  tree felling  of the teak.  This work needs much physical  labor.  Grandjean (1982) states that an extreem  physical  exertion  needs energy about  4,500 kcal/day.In order to continue  teak production it is needed to improve welfare of  the laborer by giving a better nutrition.A study  was conducted  to evaluate the effect of calorie intake on the performance  of the laborer and data were analyzed by using tabulation. The result showed that eating frequency are highly significant for teak tree fellers productive  working hour, age group of  18-40 years  with their average productive  working hours were 5 hours, 9 minutes and 29 seconds for  two times eating  frequencies.  Further  the average of 6 hours, 21 minutes and 41 seconds for  three times eating  frequencies,  and for age group 40 years up were 4 hours, 37 minutes and 25 seconds for  two times eating frequencies  and 5 hours,  10 minutes  and 36 seconds for  three times eating frequencies